Immigration and the Common Profit: Native Cloth Workers, Flemish Exiles, and Royal Policy in Fourteenth-Century London. (17th October 2016) - Lambert, Bart; Pajic, Milan
Abstract: This article reconstructs a crucial episode in the relationship between the English crown, its subjects and the kingdom's immigrant population. It links the murder of about forty Flemings in London during the Peasants' Revolt in June 1381 to the capital's native cloth workers' dissatisfaction with the government's economic immigration policy. We argue that, in the course of the fourteenth century, the crown developed a new policy aimed at attracting skilled workers from abroad. Convinced that their activities benefited the common profit of the realm, the crown remained deaf to the concerns of London's native weavers, who claimed that the work of exiled Flemish cloth workers in the city encroached on their privileges. Confronted for more than twenty-five years with political obstruction, the native weavers increasingly resorted to physical aggression against their Flemish counterparts, which came to a dramatic conclusion in 1381. The dissatisfaction of London's cloth workers and the massacre of the Flemings thus had much in common with the frustrations over the royal government's policy that had been fermenting for decades among many other groups in society: all came to the surface during the Peasants' Revolt.